A review of cinnabar (HgS) and/or realgar (As4S4)-containing traditional medicines. (10th January 2018) - Liu, Jie; Wei, Li-Xin; Wang, Qi; Lu, Yuan-Fu; Zhang, Feng; Shi, Jing-Zhen; Li, Cen; Cherian, M. George
Abstract: Ethnopharmocological relevance: Herbo-metallic preparations have a long history in the treatment of diseases, and are still used today for refractory diseases, as adjuncts to standard therapy, or for economic reasons in developing countries. Aim of the review: This review uses cinnabar (HgS) and realgar (As4 S4 ) as mineral examples to discuss their occurrence, therapeutic use, pharmacology, toxicity in traditional medicine mixtures, and research perspectives. Materials and methods: A literature search on cinnabar and realgar from PubMed, Chinese pharmacopeia, Google and other sources was carried out. Traditional medicines containing both cinnabar and realgar (An-Gong-Niu-Huang Wan, Hua-Feng-Dan); mainly cinnabar (Zhu-Sha-An-Shen Wan; Zuotai and Dangzuo), and mainly realgar (Huang-Dai Pian; Liu-Shen Wan; Niu-Huang-Jie-Du) are discussed. Results: Both cinnabar and realgar used in traditional medicines are subjected to special preparation procedures to remove impurities. Metals in these traditional medicines are in the sulfide forms which are different from environmental mercurials (HgCl2, MeHg) or arsenicals (NaAsO2, NaH2 AsO4 ). Cinnabar and/or realgar are seldom used alone, but rather as mixtures with herbs and/or animal products in traditional medicines. Advanced technologies are now used to characterize these preparations. The bioaccessibility, absorption, distribution, metabolism and elimination of these herbo-metallic preparations are different from environmental metals. The rationale of including metals in traditional remedies and their interactions with drugs need to be justified. At higher therapeutic doses, balance of the benefits and risks is critical. Surveillance of patients using these herbo-metallic preparations is desired. Conclusion: Chemical forms of mercury and arsenic are a major determinant of their disposition, efficacy and toxicity, and the use of total Hg and As alone for risk assessment of metals in traditional medicines is insufficient. Graphical abstract: Highlights: Cinnabar and realgar in traditional medicines differ from environmental metals. Minerals are seldom used alone but as mixtures with herbs and animal products. HgS or As4 S4 differ from HgCl2 and MeHg or NaAsO2 in disposition and toxicity. Pharmacology of adding minerals in traditional remedies needs investigation. Balance the benefits and risks are critical in the use of herbo-metallic mixtures.